A SYNERGITY MODEL FOR WOMEN FISHERMAN ENTREPRENEURSHIP GROWTH THROUGH THE BUSINESS OF VARIOUS PROCESSED SEA FISH PRODUCTS - Yuyus Suryana; Kartib Bayu (KOMITMEN: Jurnal Ilmiah Manajemen, 2026)
Coastal areas are areas inhabited by communities with distinctive family characteristics whose days are dominated by women and children. Some men, namely husbands and teenagers, spend much of their time at sea. The involvement of women in making a living for families in coastal areas or fishing villages is inseparable from the gender division of labor system that applies in local communities. The aim of the research is to obtain a synergy model for the growth of fisherman women entrepreneurs. The research method used is descriptive research and treatment research. The unit of analysis is the women of fishermen with a sample size of 20 respondents. The analysis technique used is descriptive and quantitative statistics. The research location is in Palabuhanratu District, Sukabumi Regency. The results showed that the program synergy model between local government, CSR, financial institutions, marketing institutions and community empowerment institutions tends to be more effective and efficient in growing fisherwomen entrepreneurs, In women, fishermen have grown interest and have pioneered businesses independently to produce variants of processed seafood products so that they can use their time well and able to help their families financially. The resulting product marketing is facilitated by PT. Sarana Rezeki Prima through its Outlets both in Sukabumi Regency and outside Sukabumi Regency. Synergy The Fishermen Women Entrepreneurial Development Program is considered quite effective, it is suggested that it can be used as a model for entrepreneurial growth to be applied to other CSR programs with the same or different goals.